Influence of contact interaction character on residual stresses arising over damaged area in composite plate (Fracture and Structural Integrity, 2025)
New data concerning the values of residual stresses that arise as a result of the contact interaction of a spherical indenter and a flat surface of composite plate have been obtained. The studies are performed for both static indentation and impact influence of a spherical indenter into a flat surface of coupons made of carbon fibre reinforced polymer with cross-ply stacking sequence. The high-quality interference fringe patterns, generated by through hole drilling in contact interaction zone, which are essential for residual stress deriving are visualized and quantitatively processed both inside and outside the contact dimple. The distributions of residual stresses obtained during static and impact contact interaction, which leads to the appearance of dimples of almost the same diameter, are compared. A comparison of the values of the principal residual stress components corresponding to the contact interaction of similar composite plates with a spherical impactor of different diameters for the same impact energy is presented. Several factors have been identified that relate the decrease in the residual strength of damaged specimens to the values of the residual stress components. Evaluation of the influence of coupon’s thickness as well as an impact energy level on the residual stress values inherent in the vicinity of contact dimple is presented.
Keywords: Composite materials; Contact interaction; Impact damage; Residual stresses; Hole drilling method; Speckle-pattern interferometry